Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Dengan Citra Merek Sebagai Variabel Intervening Pada Skincare Acnes : Studi Kasus Pada Obat Jerawat Merek Acnes Di Kota Padang - Hasmita Sari; Yulasmi Yulasmi; Mardhatila Fitri Sopali (Universitas 45 Surabaya, 2024)
The study is titled Influence of Product Quality And Price On Purchasing Decisions With Brand Image As Intervening Variable In Skincare Acnes (Case Study On Acne Drugs In Padang City). The aim of this study was to know and attempt to analyze the Effect of Product Quality And Price On Purchasing Decisions With Brand Image As Intervening Variable In Skincare Acnes (Case Study On Acne Medicine In Padang City). The study is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The method of data collection was through interviews and circulating questionnaires, with a sample of 80 respondents. The results of the study found that there is a positive and significant influence between Product Quality and Brand Image. There is a positive and significant influence of Price on Brand Image. There is a positive and significant influence between Product Quality and Purchasing Decisions. There is no positive and significant influence of the price on the purchase decision. There is a positive and significant influence between Brand Image on Purchasing Decisions. Brand Image mediates Product Quality to Purchase Decisions. Brand Image mediates Price to Purchase Decisions.